Preparation Time and Sex In Test Interpretation - Williams, Vernon (Canadian Journal of Counselling and Psychotherapy, 2012)
In view of in conclusive results obtained in previous test interpretation studies, a more highly controlled study at a simpler level seemed desirable.Subjects completing a master's degree in counseling with prior counseling experience served as client and counselor under two different conditions. In the first, the counselor had twenty minutes to examine the profile; in the second, a minimum of one hour. Of six hypotheses, the one confirmed held that when more prepared, the counselor would communicate in "expert" fashion; when less prepared, in equalitarian fashion. Results were examined also from the point of view of counselor and client sex.